2021
DOI: 10.3390/cancers13071581
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma and MiRNAs

Abstract: Glioblastoma (GB) is one of the most common types of lethal brain tumors. Although several treatment options are available including surgery, along with adjuvant chemo and radiotherapy, the disease has a poor prognosis and patients generally die within 14 months of diagnosis. GB is chemo and radio resistant. Thus, there is a critical need for new insights into GB treatment to increase the chance of therapeutic success. This is why microRNA (miRNA) is being potentially considered in the diagnosis and treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 68 publications
0
19
0
1
Order By: Relevance
“…Seven years after the discovery, the first human-encoded miRNA Let-7 was described [ 61 ]. Currently, more than 3000 miRNAs are known to be present in the human genome and involved in numerous biological processes in almost all body fluids [ 62 , 63 ]. In 2013, the first miRNA mimic MRX34 (mimic of endogenous miR-34 that suppresses oncogenesis) entered into the clinical trials [ 64 ].…”
Section: Mirnas Targeting Dkk1 Expressionmentioning
confidence: 99%
“…Seven years after the discovery, the first human-encoded miRNA Let-7 was described [ 61 ]. Currently, more than 3000 miRNAs are known to be present in the human genome and involved in numerous biological processes in almost all body fluids [ 62 , 63 ]. In 2013, the first miRNA mimic MRX34 (mimic of endogenous miR-34 that suppresses oncogenesis) entered into the clinical trials [ 64 ].…”
Section: Mirnas Targeting Dkk1 Expressionmentioning
confidence: 99%
“…We found that miR-148a and miR-92a have been reported by our previous GBM study using the relative regression method 27 . In another study, miR-92 was also reported 42 . Of course, the presence of miR-21 and miR-10b among these miRNAs was the beginning of this study, and it is also a feedback support for the results obtained.…”
Section: Discussionmentioning
confidence: 88%
“…In this case, some of the miRNAs acted as apoptotic genes, suppressing the proliferation and survival of glioblastomas or silencers of anti-apoptotic genes, thus favoring tumor growth. This potentiates the use of miRNA signatures as diagnostic biomarkers for glioblastoma, primarily with the use of liquid biopsies, which are easily obtainable [ 4 ]. miRNAs have been shown to regulate epithelial to mesenchymal transition (EMT) [ 5 ], a process whereby epithelial cells undergo biological processes that allow them to take on the phenotype of mesenchymal stem cells and adopt their enhanced migratory ability, invasive capacity and increased ability to resist apoptosis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%